Developing an Organizational Knowledge Audit Focused on Core Processes and Professional Development (Journal of Qualitative Research in Business Law, Eco-Fin, Accounting, and Statistics, 2024)
Objectives: reflect the main elements of a knowledge audit that combines the main processes with professional development indicators that could identify those components of human capital that should be favored.Methods: the main elements of a knowledge audit that combines the main processes with professional development indicators were analyzed. An approach is proposed that allows the identification of the components of human capital that must be enhanced. No other methodology has been identified with this orientation.Results: the image of the strengths and weaknesses of the organizations, as well as the knowledge necessary in each process, provide the basis for the regulation of organizational processes and the necessary human and technological components. It contributes to the identification of knowledge gaps as well as the cultural elements that must be addressed. It is a solid guideline for programming professional development actions that could solidify the future design of these processes and contribute to the professional competencies of the members of these communities of practice.Conclusions: This is a solid guide for professional development practice, oriented towards the future development of organizational processes and contributes to the growth of the professional competencies of these communities of practice. The organization's strategic platform has been enriched with the identification of the strengths and weaknesses of its processes from different points of view. This methodological approach will be applied in different cases to possible adjustments analyzed in its design.